Cerebral pyogranuloma associated with systemic coronavirus infection in a ferret. (4th June 2015) - Gnirs, K.; Quinton, J. F.; Dally, C.; Nicolier, A.; Ruel, Y.
Abstract : A 2‐year‐old male ferret was presented with central nervous system signs. Computed tomography (CT) of the brain revealed a well‐defined contrast‐enhancing lesion on the rostral forebrain that appeared extraparenchymal. Surgical excision of the mass was performed and the ferret was euthanised during the procedure. Histopathology of the excised mass showed multiple meningeal nodular lesions with infiltrates of epithelioid macrophages, occasionally centred on degenerated neutrophils and surrounded by a broad rim of plasma cells, features consistent with pyogranulomatous meningitis. The histopathological features in this ferret were similar to those in cats with feline infectious peritonitis. Definitive diagnosis was assessed by immunohistochemistry, confirming a ferret systemic coronavirus (FSCV) associated disease. This is the first case of coronavirus granuloma described on CT‐scan in the central nervous system of a ferret.